Rapid video copy detection on compressed domain - ZHANG Yong-dong; ZHANG Dong-ming; GUO Jun-bo; TANG Sheng (Tongxin xuebao)
To reduce the detection time efficiency under large scale data environment, a rapid algorithm was proposed on compressed domain using a two-level hierarchical detection scheme.The ordinal measures of DCT coefficients were adopted as visual features for similarity-matching in order to reduce the computational load in video decoding.Inverted indexing structure was used to accelerate the first level detection process.The experiment results show, compared with the previous algorithm, the algorithm can improve the detection speed obviously with the similar detection precision.